2021
DOI: 10.1094/php-07-20-0059-s
|View full text |Cite
|
Sign up to set email alerts
|

Six Species of Diaporthe Associated with Phomopsis Stem Canker of Sunflower in Southern Pampean Region of Argentina

Abstract: A survey of 67 commercial fields in 19 locations was conducted in the southern Pampean region of Argentina for Phomopsis stem canker of sunflower (Helianthus annuus L.) between 2014 and 2019. A total of 210 plants having typical symptoms of Phomopsis stem canker were randomly sampled, and fungal isolation was performed. Of the 187 isolates of Diaporthe that were recovered, 94% of the isolates showed morphological characteristics similar to D. helianthi, 3% to D. gulyae, 1% to D. caulivora, 1% to D. sojae, 0.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, in 2015 it re-emerged in the southern Pampas [ 26 ]. A recent study found the presence of six Diaporthe species associated with sunflower diseases in the southeast Pampas region, including D. helianthi, Diaporthe gulyae, Diaporthe kongii, Diaporthe sojae, Diaporthe caulivora, and Diaporthe longicolla [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in 2015 it re-emerged in the southern Pampas [ 26 ]. A recent study found the presence of six Diaporthe species associated with sunflower diseases in the southeast Pampas region, including D. helianthi, Diaporthe gulyae, Diaporthe kongii, Diaporthe sojae, Diaporthe caulivora, and Diaporthe longicolla [ 27 ].…”
Section: Introductionmentioning
confidence: 99%